أثر تعدّد الآراء النّحويّة في تفسير الآيات القرآنيّة - عوض, سامي; مطره جي, ياسر (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
إنّ منطلقَ الدّراسةِ المُعْتَمَدَةِ في هذا البحثِ في بيانِ أثرِ الاختلافِ بينَ النَّحْويّينَ في الأوجهِ الإعرابيّة في تفسيرِ الآياتِ القرآنيّةِ، إنّما هو اكتناهٌ لمعاني النَّحْوِ في الإفصاحِ عَنْ تفسيرِ العديدِ مِنْ آيِ الذكرِ الحكيمِ؛ إذ لا يخفى على دارسِ العربيّةِ الارتباطُ الوثيقُ بينَ المعنى والحالةِ الإعرابيّةِ. وَمَنْ يتتبّعْ نشأةَ النّحْوِ الأولى، وتقعيدَ العلماءِ له، يلحظْ أنَّ تعدّد الأوجه في تحليل أحد العناصرِ التركيبيّة أمرٌ شائعٌ ومألوفٌ، فيرى أحياناً أنَّ أحدهم قد يجيزُ غيرَ وجهٍ في عنصرٍ ما، كما يألف الخلاف بينهم في أثناء التحليل، ولذلك شاعَ الجواز في تحليلهم، وكثر الأخذ والرّد بالترجيح أو التّضعيف أو الرّفض؛ فكان إثر ذلك، من البدهيّ والطبعيّ أن تختلفَ آراؤهم، وتتشعّبَ مواقفُهُمْ، وتتعدّدَ أوجهُهُم في تحليلاتهم، راسمين للّغةِ في ضوءِ هذه الاختلافات كلِّها، الغناءَ في التنوّعِ المعنويِّ، والنّماءَ في التعبيرِ الدّلاليِّ. ويهدفُ هذا البحثُ إلى بيان كيفيّةِ استخدام هذه اللغةِ لتحقيق أهداف النصّ القرآنيِّ وغاياته، بدراسةٍ تربطُ النِّظامَ النَّحْويَّ بالطريقة التي وُظِّفَ فيها هذا النظامُ لأداء المعاني، في ضوء إبراز العلاقة النحويّة بين الإعراب والمعنى؛ إذ كلّما تعدّد إعرابُ الكلمة، تعدّد المعنى الواحد والعكس؛ لأنّ النّحْوَ شأنُ العلوم الإسلاميّة الأخرى، نشأ لفهم القرآن الكريم، والبحث عن كلّ ما يفيد في استنطاق نصوصه، باعتباره أعلى ما في العربيّةِ مِنْ بيانٍ. This study shows the differences among the linguists in the linguistic possibilities of interpreting the Quranic verses. It is obvious to any scholar who studies Arabic the tight connection between the meaning and the linguistic case. Following the first rise of the linguistics and the establishment of its rules by the linguists, one may observe that the numbers of issues studying one of the compound elements is a common and familiar thing. He sometimes observes that one of the linguists may allow more than one possibility in one element. He may also observe the differences during analysis. So, variety becomes common in the analysis. There was much of acceptance and rejection. Thus, it is natural that opinions may differ and have many possibilities in the analysis to give the language, through that these differences, richness in the variety of meaning. This research aims to show how to use language to achieve the ends and goals of the Quranic text through studying what connects the linguistic system with the way in which the system was employed to serve the meanings in the light of showing the linguistic relation between the meaning and the linguistics. Whenever the word possibility varies, the meaning varies too, and vice versa. Linguistics, as the other Islamic Sciences, was found to understand the Holy Quran and look for the useful things that help in explaining its texts. This is because the Quran has the highest degree of eloquence in Arabic.